TREATMENT OF ELECTRONIC EVIDENCE AFTER A JUDGE'S DECISION WHICH HAS PERMANENT LEGAL FORCE IN CRIMINAL CASES - Fanidia Tumanggor; Faizin Sulistio; Patricia Audrey (CV. RADJA PUBLIKA, 2025)
Advances in information and communication technology have significantly influenced legal developments, particularly in the area of ​​evidence in criminal justice processes. The use of electronic evidence as evidence in various criminal cases poses challenges related to the clarity and adequacy of the legal framework in Indonesia. This study aims to examine the extent to which Indonesian law accommodates the existence of electronic evidence and how judges determine its legal status and treatment after a criminal verdict has become final and binding. The study focuses on the question of whether it is sufficient to seize electronic data together with the electronic device or whether a normative separation between the physical device and the electronic data within it is necessary, as is the practice in the Netherlands and France. In this context, it is important to analyze whether existing legal provisions provide legal certainty and strike a balance between the interests of law enforcement and the protection of individuals' rights to personal data, information, and/or electronic documents contained in seized electronic devices. Through a normative juridical and comparative legal approach, this study finds that legal regulations in Indonesia do not specifically regulate the treatment of electronic data in court decisions. Therefore, regulatory reform is needed to ensure the protection of each individual's constitutional rights and strengthen the integrity of the evidentiary system in electronic-based criminal cases.